Patterns of Musculoskeletal Disorders among Staff Nurses in the Emergency Department in Saudi Arabia: A Cross-sectional Study - Afaf Mufadhi Alrimali; Nashi Masnad Alreshidi; Aljazi Albshri Alshammari; Aeedah Rfadah Alenzy; Riya Thomas; May Ann Dinoy; Fouz Aziz Alanzi; Eddieson Pasay-an (Nurse Media: Journal of Nursing)
Background: The physically demanding and high-stress environment of Emergency Departments (EDs) significantly contributes to the heightened risk of musculoskeletal disorders (MSDs) among ED nurses. Despite this known association, there is a lack of comprehensive understanding of the prevalence rates and contributing factors within ED settings in Saudi Arabia, necessitating further investigation.